Supramolecular nanomedicine in the intelligent cancer therapy: recent advances and future - Li, Shuo; Wang, Yujiao; Li, Chao; Zhou, Binghao; Zeng, Xiaoxi; Zhu, Hong (Frontiers in Pharmacology, 2024)
In recent years, the incidence of cancer has been increasing year by year, and the burden of the disease and the economic burden caused by it has been worsening. Although chemotherapy, immunotherapy, targeted therapy and other therapeutic means continue to progress, they still inevitably have problems such as high toxicity and side effects, susceptibility to drug resistance, and high price. Photothermal therapy and photodynamic therapy have demonstrated considerable advantages in cancer imaging and treatment due to their minimally invasive and selective nature. However, their development has been constrained by challenges related to drug delivery. In recent times, drug delivery systems constructed based on supramolecular chemistry have been the subject of considerable interest, particularly in view of their compatibility with the high permeability and long retention effect of tumors. Furthermore, the advantage of dissociating the active ingredient under pH, light and other stimuli makes them unique in cancer therapy. This paper reviews the current status of supramolecular nanomedicines in cancer therapy, elucidating the challenges faced and providing a theoretical basis for the efficient and precise treatment of malignant tumors.